2013
DOI: 10.1037/a0029847
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the social effects of emotion regulation: The mediating role of authenticity for individual differences in suppression.

Abstract: Individuals differ in the strategies they use to regulate their emotions (e.g., suppression, reappraisal), and these regulatory strategies can differentially influence social outcomes. However, the mechanisms underlying these social effects remain to be specified. We examined one potential mediator that arises directly from emotion-regulatory effort (expression of positive emotion), and another mediator that does not involve emotion processes per se, but instead results from the link between regulation and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
252
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(281 citation statements)
references
References 96 publications
(141 reference statements)
16
252
1
6
Order By: Relevance
“…(p. 471) In line with this conclusion, Ilies, Cursue, Dimotakis, and Spitzmuller (2013) subsequently found that managers' emotional experiences and relational authenticity were indeed favorably associated with their subordinates' extra work efforts and their perceptions of their managers' effectiveness. Taken together, these findings and conclusions align with those in the broader literature on emotion regulation which has consistently found that the deliberate suppression of emotion is associated with elevated blood pressure as well as with impaired social functioning and inhibited relationship formation (Butler et al, 2003;English & John, 2013;Srivastava, Tamir, McGonigal, John, & Gross, 2009). However, to the best of our knowledge, no prior studies have conjointly assessed the contributions of adult attachment security and of both experienced and expressed forms of work authenticity to the well-being of business managers.…”
Section: Surface Acting: the Self-expressive Component Of Work Authensupporting
confidence: 87%
“…(p. 471) In line with this conclusion, Ilies, Cursue, Dimotakis, and Spitzmuller (2013) subsequently found that managers' emotional experiences and relational authenticity were indeed favorably associated with their subordinates' extra work efforts and their perceptions of their managers' effectiveness. Taken together, these findings and conclusions align with those in the broader literature on emotion regulation which has consistently found that the deliberate suppression of emotion is associated with elevated blood pressure as well as with impaired social functioning and inhibited relationship formation (Butler et al, 2003;English & John, 2013;Srivastava, Tamir, McGonigal, John, & Gross, 2009). However, to the best of our knowledge, no prior studies have conjointly assessed the contributions of adult attachment security and of both experienced and expressed forms of work authenticity to the well-being of business managers.…”
Section: Surface Acting: the Self-expressive Component Of Work Authensupporting
confidence: 87%
“…Indeed, inhibited emotional expression has been shown to make it more likely for others to perceive the inhibited person as untrustworthy or inauthentic (e.g., English and John, 2013) and to reduce social connectedness (e.g., Mauss et al, 2011). It has also been hypothesized that people who show reduced positive facial expression are trying to avoid people's attention .…”
Section: Discussionmentioning
confidence: 99%
“…Emotion suppression can give a participant a slightly negative view of past experience, making him or her more suspicious of later studies. English and John (2013 ) argued that emotion suppression results in a diff erence between the inner self and outward behavior. This diff erence in self led to a social cost, i.e., not found in emotion reappraisal.…”
Section: Individual Diff Erences Aff Ecting Consent Readingmentioning
confidence: 99%